Histopathological evaluation of bone regeneration using human resorbable demineralized membrane - Tatić Zoran; Stamatović Novak; Bubalo Marija; Jančić Snežana; Račić Alek; Miković Nikola; Tatić Natalija; Rakić Mia (Vojnosanitetski Pregled)
Background/Aim. Filling a bone defect with bone substitution materials is a therapy of choice, but the infiltration of connective tissue from the mucoperiostal flap may compromise a healing of bone substitutions with bony wall defects. Application of membrane as a barrier is indicated as a solution to this problem. The aim of this study was to show a pathohistological view of bone regeneration and the significance of human resorbable demineralized membrane (HRDM), 200 μ thick in bone regeneration regarding mandibular defects in an experiment on dogs. Methods. The experiment was performed on six dogs. Bone defects were created in all six dogs on the right side of the mandible after the elevation of the mucoperiostal flap. One defect was filled with human deproteinised bone (HDB), and in between HDB and soft tissue RHDM of 200 μ thick was placed. In the second defect, used as a control one, only HDB without RHDM was placed. Two dogs were sacrificed two months after the surgery, another two dogs four months after the surgery and the last two dogs six months after the surgery. After that, samples of bone tissue were taken for histopathological analysis. Results. In all the six dogs with defects treated with HDB and RHDM the level of bone regeneration was much higher in comparison with the control defects without RHDM. Conclusion. Membrane, as a cover of bony defect, is useful and benefits bone regeneration. Bony defects covered with RHDM show better bony healing despite the fact that bone regeneration was not fully complete for as long as six months after the RHDM implantation.